Labour reforms and integration processes in the member states of the OAS : 1980-2000 - Ciudad, Adolfo (ILO LimaPE, 2002)
Addresses the key elements that helped shape the labour relations system as we have known it throughout the XX century, up to the labour reforms recently carried out in this region. Focuses on the implementation of structural reforms as part of the integration of the region to the world markets, and discusses fundamental issues such as flexibility and labour institutions. Examines the changes implemented in the region's labour legislation. Analyzes the main institutions affected by the reforms in the areas of individual rights and collective labour rights. Evaluates the impact of the reforms.